Design ideas for baby rooms - 4 0 16; 5 Creative Homeowner Press (Upper Saddle River, N.J. : Creative Homeowner, 2009)
Top architects and interior designers offer tips for creating a beautiful, functional nursery, with planning tips and suggestions for every budget and style.
Make room for baby -- Color and pattern -- Furniture and storage -- Walls, windows, and floors -- Keeping baby cozy -- Toddlers' rooms -- Keeping them safe -- Health and special needs.
Keywords: 2 -- 0; 6; Nurseries.;Children's rooms.;Interior decoration. -- 20; 20; 2